The Effectiveness Of Contextual Teaching And Learning To Teach Reading Comprehension For Student Grade Eight MTSN 5 Janapria In Academic Year 2022/2023 - Karyawan Putraidi; Ria Hendriani (Program Studi Pendidikan Bahasa Inggris FKIP, 2024)
The objective of the research is to know the influence of optimizing of Contextual Teaching and Learning in student reading improvement. This research is quantitative research using experimental method. Subjects of this research are 42 students that are divided into two classes, namely control class (21) and experiment class (21). The researcher used cluster random sampling technique to determine the sample. The researcher collected the data using test and observation. Furthermore, the data was analyzed by using descriptive statistical analysis technique and the hypothesis used t-test. Hypothesis test shows that contextual teaching and learning is more effective to improve students’ reading comprehension. This can be seen from the results of test score, it shows that the experimental class which was given treatment using contextual teaching and learning got higher score than control class without contextual teaching and learning. It was obtained that rxy is 0.456 and then rxy is consulted to the critical value for r table of Product Moment to examine whether rxy value is significant or not. The value of r table with N = 21 and the 5% significant level is 0.312. Therefore, it can be concluded that rxy is greater than r table in the other words, 0.456 is greater than 0.312. The result of this study is expected to be information and inputs for the institution, teachers, students and all of the circles to improve students’ achievement.